A new single stage single phase power factor corrected and isolated AC-DC converter based on resonance and soft switching - Bodur, Haci; Akboy, Erdem; Aksoy, Ismail (Tubitak Scientific & Technological Research Council Turkey, 2016)
In this paper, a new single stage single phase power factor corrected and isolated AC-DC converter based on resonance and soft switching (SS) is presented. In fact, a new concept for power factor corrected converter is proposed in this study. This converter provides power factor correction (PFC) by using a switch and a fully resonant circuit. It also provides regulated and isolated output voltage with direct power transfer by using a second switch and forward and flyback topologies based on resonance. Both switches in the converter are controlled with the same closed loop and the time multiplexing, and are switched with soft switching dominantly because of resonance. The input or PFC switch is turned on and off under zero current switching (ZCS) due to the resonant circuit. The output switch is turned on with ZCS due to resonance, and unfortunately is turned off with hard switching. The operation principle, detailed steady state analysis, and design procedure of the new PFC converter are presented. The theoretical analysis is verified by a prototype of the new converter using 125 W and 100 kHz.
Keywords: Power factor correction; soft switching; direct power transfer; ELECTRONIC BALLAST; CIRCUIT; VOLTAGE; FAMILY; Computer Science; Engineering